Study on Mechanical Characteristics and Construction Control of the Railway Overlapping Tunnels - Fengjie, Yuan; Yang, Liu; Qianwei, Xu; Yuanlin, Zheng; Lisheng, Hu; Ping, Zhao; Yuebang, Cui (Frontiers in Earth Science, 2022)
Tunnels are widely used in transportation infrastructure construction projects. With the increase in construction efforts, a distribution form of super-close tunnels overlapping up and down gradually appears. The upper and lower overlapped tunnel engineering has the disturbing effect of the later-built tunnel on the surrounding stratum and the existing tunnel, and has the problem of causing its secondary lining to crack, which will cause potential hazards to the tunnel project, and even cause the overall damage of the tunnel structure if handled improperly. In this paper, it combines a new tunnel project in Chongqing, China, which spans an existing lower tunnel at a close distance, aiming at the engineering problem of concentrated longitudinal cracks in the secondary lining of the lower tunnel. By using the finite element method (FEM), the changes of the tunnel vault displacement, invert deformation and horizontal convergence of the transverse bracing during the construction of overlapping tunnels were studied, and combined with the construction-induced stratum shear stress and plastic zone distribution characteristic indexes, the stratum disturbance effect of the excavation process was analyzed. At the same time, combined with the field records, the stress distribution characteristics of the secondary lining of the existing tunnel caused by the later-built tunnel and the cause and spatial distribution of the longitudinal cracks of the lining structure were analyzed. The results of the study has shown that the bias of the upper later-built tunnel construction on the lower tunnel is the main reason for the cracking of the secondary lining.